Study of treatment with hyaluronic acid combined with platelet rich plasma in the in vivo regeneration of defects in articular discs of temporomandibular joint - El Abras Ankha, Milagros del Valle [UNESP]; Prado, Renata Falchete do [UNESP]; Barros Lima, Vinicius de Almeida [UNESP]; Carvalho, Yasmin Rodarte [UNESP]; Reis de Vasconcellos, Luana Marotta [UNESP] (Elsevier B.V., 2020)
The aim of this study was to evaluate the in vivo repair using an experimental model of osteoarthritis of the temporomandibular joint in rabbits, treated with hyaluronic acid (HA), isolated or combined with platelet rich plasma (PRP). Forty New Zealand rabbits were divided into 4 groups: G1 - normal TMJ, G2 - lesion / untreated, G3 - lesion / HA, and G4 - lesion / PRP + HA. The disc and the condyle were evaluated using radiographies, macro and microscopic analysis through routine histotechnique, Picrosirius red staining and immunohistochemistry. The results were evaluated by descriptive and inferential statistics. Macroscopically, the disc in the treated groups presented, in most of the specimens, partial or total filling of the defect. Histological analysis confirmed the presence of mineralized material, near and distant perforation, as well as decreased cellularity and fibrosis. The collagen I was demonstrated in higher amounts when compared to type III collagen, independently of the group and period evaluated; in the condyle, G3 and G4 presented significant higher percentage of type I collagen, than G2. In conclusion, the groups that were treated with HA and PRP combined with HA presented no significant differences in microscopic pattern. The macroscopic finding that in some samples in HA treated group and one sample in PRP + HA group presented complete filling of the perforation let us to conclude that new experiments adding more sensitive methods may clear the influence of these treatments in reduce the damage in the osteochondral surface related the lesioned disc.
Keywords: Osteoarthritis; Temporomandibular joint; Tissue regeneration; Platelet rich plasma; Hyaluronic acid